Analysis of Lifestyle Classification Using a Decision Tree Approach - Afriosa Syawitri; Siti Rahmi Hidayatullah; Miranda Nuraini (Intellect : Indonesian Journal of Learning and Technological Innovation, 2025)
Lifestyle related health issues continue to increase, highlighting the need for data-driven approaches that not only classify lifestyle patterns but also provide interpretable insights to support health-related decision making. This study aims to develop an interpretable lifestyle classification model using the Decision Tree algorithm, with a specific analytical focus on identifying dominant behavioral factors and their hierarchical relationships in distinguishing healthy and unhealthy lifestyles. The dataset was collected through a questionnaire survey involving 130 respondents representing diverse lifestyle behaviors. Initially, 23 attributes measured using Likert scales were used to capture multiple aspects of lifestyle. To improve analytical clarity and reduce data complexity, the attributes were transformed by grouping conceptually related items into four main behavioral domains: diet, physical activity, sleep patterns, and mental health. Personal demographic attributes were excluded from the modeling process due to their limited relevance to lifestyle behavior and their potential to introduce classification bias. Within each domain, sub-attributes were aggregated using mean values to generate stable composite scores, a methodologically appropriate approach given the non-parametric and threshold-based characteristics of the Decision Tree algorithm. The applied to reduce overfitting. The results indicate that the proposed model achieved an accuracy of 84.62% and a weighted average F1-score of 0.84, demonstrating balanced classification performance. The model showed strong recall in identifying healthy lifestyles, while limitations related to generalizability remain. Transformed dataset was divided into training and testing sets using a 70:30 hold-out validation strategy. Model construction employed the entropy criterion and information gain for attribute selection, with complexity control. Abstrak Masalah kesehatan terkait gaya hidup terus meningkat, menyoroti perlunya pendekatan berbasis data yang tidak hanya mengklasifikasikan pola gaya hidup tetapi juga memberikan wawasan yang dapat ditafsirkan untuk mendukung pengambilan keputusan terkait kesehatan. Penelitian ini bertujuan untuk mengembangkan model klasifikasi gaya hidup yang dapat diinterpretasikan menggunakan algoritma Decision Tree, dengan fokus analitis khusus untuk mengidentifikasi faktor perilaku dominan dan hubungan hierarkisnya dalam membedakan gaya hidup sehat dan tidak sehat. Kumpulan data dikumpulkan melalui survei kuesioner yang melibatkan 130 responden yang mewakili beragam perilaku gaya hidup. Awalnya, 23 atribut yang diukur menggunakan skala Likert digunakan untuk menangkap berbagai aspek gaya hidup. Untuk meningkatkan kejelasan analitis dan mengurangi kompleksitas data, atribut diubah dengan mengelompokkan item yang terkait secara konseptual menjadi empat domain perilaku utama: diet, aktivitas fisik, pola tidur, dan kesehatan mental. Atribut demografis pribadi dikecualikan dari proses pemodelan karena relevansinya yang terbatas dengan perilaku gaya hidup dan potensinya untuk memperkenalkan bias klasifikasi. Dalam setiap domain, sub-atribut dikumpulkan menggunakan nilai rata-rata untuk menghasilkan skor komposit yang stabil, pendekatan yang sesuai secara metodologis mengingat karakteristik non-parametrik dan berbasis ambang batas dari algoritma Pohon Keputusan. Himpunan data yang diubah dibagi menjadi set pelatihan dan pengujian menggunakan strategi validasi penahanan 70:30. Konstruksi model menggunakan kriteria entropi dan perolehan informasi untuk pemilihan atribut, dengan kontrol kompleksitas diterapkan untuk mengurangi overfitting. Hasil menunjukkan bahwa model yang diusulkan mencapai akurasi 84,62% dan skor F1 rata-rata tertimbang 0,84, menunjukkan kinerja klasifikasi yang seimbang. Model ini menunjukkan ingatan yang kuat dalam mengidentifikasi gaya hidup sehat, sementara keterbatasan yang terkait dengan generalisasi tetap ada.